The Evaluation of Sustainable Professional Development Program to Enhance English Teachers’ Ability - Wulandari, Astry; Gailea, Nurhaeda; Hidayat, Sholeh (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
This research is made based on the teachers’ problem in learning process. There are some problems emerged such as teachers lack of understanding in learning steps and how to write and read for the beginner. On the other hand, teachers also do not understand how to make the appropriate lesson plan. The intentions of this research consist of knowing the implementation of the ministry of religion affair program towards students’ learning outcome and the improvement of teachers’ skill. However, this study is using CIPP evaluation model which is developed by Stufflebeam. This research conducted to English teachers at Islamic school in Serang city. There are twenty-seven teachers who followed this program. The choosing of participants is based on the data from the Information System for Educators and Education Personnel or we called SIMPATIKA. The data is got from the participants’ test, instruments and the documentation. It shows that the program gives the good impact for teachers and students’ learning outcome. There are 47% very good response and 53% good response from students related to this program and there is an increasing teachers’ ability about 27% in taking pretest and posttest. Besides, the category of teachers’ ability is very good based on smile face instrument and bull eyes.